High-energy, nutrient-dense emergency relief food product - Institute of Medicine (U.S.). Subcommittee on Technical Specifications for a High-Energy Emergency Relief Ration (Washington, D.C. : National Academy Press, 2002)
The present study was conducted by an ad hoc subcommittee of the Committee on Military Nutrition Research. The Subcommittee on Technical Specifications for a High-Energy Emergency Relief Ration was established by the Food and Nutrition Board of the Institute of Medicine in response to a request from USAID and DOD to develop technical specifications for a product for use in food relief after natural disasters or other emergency situations around the world. The specifications are to be used by both agencies in their calls for bids from U.S. food manufacturers to supply such a product.
Executive summary -- Background and charge to the committee -- Methods -- Report organization -- Recommendations -- References -- Introduction -- Project description and scope -- Origin of the study -- Need for and uses of a high-energy, nutrient-dense emergency relief food product -- References -- Nutrient content and special considerations -- Introduction -- Characteristics of target populations -- Characteristics of the emergency relief food product -- Nutrients included in the emergency relief food product specifications -- References -- Processing and packaging of the emergency food product -- Desirable characteristics of an emergency relief food product -- Processing considerations -- Microbiological considerations -- Chemical stability considerations -- Acceptability considerations -- Packaging considerations -- Cost considerations -- References -- Performance specifications -- Item description -- Performance requirements -- Prohibitions -- Processing requirements -- Packaging requirements -- Miscellaneous information -- Biographical sketches of subcommittee members.
Title from PDF title page.
Includes bibliographical references.
Support for this project was provided by the U.S. Department of the Army, Army Medical Research and Materiel Command through grant No. DAMD17-99-1-9478. The U.S. Army Medical Research Acquisition Activity, 820 Chandler Street, Fort Detrick, MD 21702-5014, is the awarding and administering acquisition office. The views presented in this publication are those of the Subcommittee on Technical Specifications for a High-Energy Emergency Relief Ration and do not necessarily reflect the position or policy of the government, and no official endorsement should be inferred.
Version viewed November 4, 2014.
eBooks on EBSCOhost
Keywords: Nutrition -- Requirements; Emergency food supply; Food relief; Medical emergencies; Disaster relief; Food Assistance -- standards; Food, Fortified -- standards; Nutritional Requirements; Emergencies; Relief Work; Alimentation -- Besoins; Aide alimentaire d'urgence.; Aide alimentaire; Urgences médicales.; Secours aux victimes de catastrophes; HEALTH & FITNESS -- Nutrition; HEALTH & FITNESS -- Diets; MEDICAL -- Nutrition; MEDICAL -- Nursing -- Nutrition; HEALTH & FITNESS -- Food Content Guides; Medical emergencies; Emergency food supply; Food relief; Nutrition -- Requirements; technical reports; Technical reports; Technical reports; Rapports techniques